دراسة أهمية مواعيد الزراعة والكثافة النباتية المؤثرة في بعض أصناف السلجم(Brassica napus L.) - د. سعد احمد محمد الدوري (University of Mosul-college of Basic Education, 2011)
In order to illustrate the Importance of studying sowing date of rapeseed crop (Brassica napus L.), yield components and quality, three cultivars including Opera, Licord and Oscar were sown from 15th September to 15th November, during two winter successive seasons 2008-2009, 2009-2010, with two plant density (62.500,125.000 plants.ha-1). The experiment carried out at AL-Quba in the west north region of Mosul city at Nineveh region. It was conducted according to factorial experiment in a randomized completely block design [cultivars(a)=3, sowing date(b)=3, plant density(c)=2] with three replications. The results could be summarized as: The results revealed that the Licord cultivar gave a high level of characters plant height, number of primary branches, number of silique per plant, leaf area(cm2plant), leaf area index, dry weight/plant (g.), number of seeds /silique, weight of thousand seed (g), total yield and oil yield (ton.ha-1) and oil percentage in both seasons 2008-2009, 2009-2010. The second planting date (mid of October) gave the highest rate of prescriptions of plant height, number of primary branches, leaf area (cm2plant), leaf area index, number of silique /plant, dry weight (g.)/plant, number of seed/silique, weight of thousand seed (g.), total yield and oil yield (ton.ha-1), While the third planting date (mid of November) gave the highest percentage of oil in seeds in both seasons. Decreasing plant density to 62.500 caused a significant increase in number of primary branches, number of silique/plant,leaf area(cm2plant) ,dry weight /plant(g.), weight of thousand seed, oil percentage in seed and yield, oil yield, While increasing plant density to 125.000 plants.ha-1 led to significant increases in plant height, leaf area index, in both seasons 2008-2009, 2009-2010.